2010
DOI: 10.3174/ajnr.a2051
|View full text |Cite
|
Sign up to set email alerts
|

Preinterventional Clopidogrel Response Variability for Coil Embolization of Intracranial Aneurysms: Clinical Implications

Abstract: BACKGROUND AND PURPOSE:Thromboembolism is one of the most serious complications in coil embolization for intracranial aneurysms, and antiplatelet premedication may reduce this complication. However, interindividual variation exists in the efficacy of CPG. This study sought to elucidate the clinical implications of preinterventional CPG response variability in patients who undergo coil embolization for intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 35 publications
5
71
0
Order By: Relevance
“…Kang et al demonstrated that a higher rate of thromboembolic complications in patients with insufficient platelet inhibition, 20 which was similar to our results despite the use of a different endovascular procedure (coil vs stent) and antiplatelet function test (VerifyNow vs TEG). Light transmission aggregometry (LTA) is considered the gold standard in the evaluation of platelet function, but it is costly and time-consuming.…”
Section: Discussionsupporting
confidence: 81%
“…Kang et al demonstrated that a higher rate of thromboembolic complications in patients with insufficient platelet inhibition, 20 which was similar to our results despite the use of a different endovascular procedure (coil vs stent) and antiplatelet function test (VerifyNow vs TEG). Light transmission aggregometry (LTA) is considered the gold standard in the evaluation of platelet function, but it is costly and time-consuming.…”
Section: Discussionsupporting
confidence: 81%
“…11,21,22 However, patients in these studies regarding antiplatelet resistance were mostly those with atherosclerotic steno-occlusive disease, especially in cardiointerventions. 23,24 Unlike atherosclerotic vessels, unruptured aneurysms do not always cause significant atherosclerotic burden.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Still, these results are controversial, and the association between antiplatelet drug resistance and diffusion lesions has not yet been fully elucidated. 11,12 Therefore, the purpose of this study was to verify the association between thromboembolic infarction and antiplatelet drug resistance after endovascular coil embolization for unruptured intracranial aneurysms. We also explored other risk factors for thromboembolic complications.…”
mentioning
confidence: 99%
“…According to the protocol of our institution, dual antiplatelet agents (clopidogrel and aspirin) were administered when stent protection was anticipated during the procedure. In patients showing poor response to clopidogrel based on the VerifyNow P2Y12 assay (Accumetrics, San Diego, California), 10 cilostazol was added. A bolus of 3000 IU of heparin was administered after femoral artery sheath placement, and intermittent boluses of 1000 IU per hour were then administered.…”
Section: Dsa and Endovascular Proceduresmentioning
confidence: 99%